Program Latihan "CERDIK" Dalam Mendeteksi Penyakit Tidak Menular (PTM) - Handayani, Luh Titi; Kurniawan, Hendra; Jumanto, Jumanto; Hidayat, Hidayat; Fatahillah, Dimas; Ascarya, Farrel (Jurnal Pengabdian Teknologi Informasi dan Kesehatan (DIANKES), 2023)
According to the World Health Organization (WHO), the four main non-communicable diseases (NCDs) are diabetes, malignancy, chronic respiratory disease, and cardiovascular disease. Service activities are carried out at the community level to play an active role in managing stability and health in the family. The method of community service activities is by taking an approach in these promotive activities through 1) analysis of knowledge, attitudes, and behavior of a Healthy and Clean Lifestyle (PHBS), 2) identification of health problems, 3) health checks, 4) making counseling media, 5) conducting counseling health, 6) FGD to form CERDIK caring community groups. The description of the results of the activity shows that several factors trigger NCDs, including most of them the elderly, a family history of hypertension, abdominal circumference in women is more than 80 cm and in men 90 cm, BMI is mostly overweight and obese, systolic pressure is more than of 140 mmHg, visceral fat of more than 10, the random blood sugar of more than 180 mg/dl, uric acid of more than 6 in women and more than 7 in men and other good health management practices such as regular health checks and uses MSG which is often in every day. Community Service activities carried out are very useful in screening non-communicable diseases which are often overlooked and trigger NCDs. This activity provides awareness exposure to the public to understand their health conditions and carry out prevention (health promotion) and rehabilitation starting with yourself and your family.